PENINGKATAN AKTIVITAS DAN HASIL BELAJAR MAHASISWA PADA MATA KULIAH ANATOMI TUMBUHAN MELALUI MODEL PEMBELAJARAN KOMPARASI YANG BERBASIS LESSON STUDY - Hanik, Nur Rokhimah (Jurnal Pendidikan Matematika dan IPA, 2016)
This study aims to improve the activity and results of student learning in the subject of Anatomy Plant through a comparative study model based lesson study. The method used is classroom action research with 4 cycles. Samples used in this study is the third semester students of regular education courses Biology FKIP Veteran Bangun Nusantara University Sukoharjo force 2012/2013 as many as 24 people. The study began in November 2013 and April 2014. The learning activities were observed in the form of discussion and presentation activities, while learning outcomes measured were the post-test results after completion of the learning process of each cycle. Data analysis techniques with comparative descriptive, comparing the results of learning and learning activity cycle with the cycle I to IV. From the results of this study concluded that the average post-test or study results from Cycle I to IV increased starting 3.47, 3.72, 3.73 and 3.85, though in terms of learning activities is still not satisfactory because it only categorized quite active for the first cycle to the active cycle III and cycle IV. Keywords: Model Comparison learning, learning activities, learning outcomes.